PENGEMBANGAN MODUL PEMBELAJARAN MODIFIKASI PERMAINAN BERBASIS QR CODE UNTUK KEMAMPUAN MOTORIK SISWA KELAS III SD NEGERI 1 SIDOHARJO - Mellin Andriana; Muhammad Supriyadi; Wawan Syafutra (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2025)
This research aims to produce a development of a QR code-based game modification learning module for students' motor skills. This type of research is Research and Development with the ADDIE development model. The subjects of this research were class III students at SD Negeri 1 Sidoharjo. Data collection techniques use interviews, observation, and questionnaires. Data analysis techniques use validity tests, practicality tests, and effectiveness tests. Based on the media validation results of the QR code-based game modification learning module for motor skills using the ADDIE Development Model, it meets the valid criteria with an average score of 0.84 with the Aiken's V validation interpretation table with high criteria. In the practicality test, teachers and students obtained an average score of 88,22% with very practical criteria. In the effectiveness trial, an average N-Gain score of 0.84 was obtained with high criteria included in the N-Gain category g>0.75. In conclusion, from the results of validation trials, teacher and student practicality test results, and effectiveness tests, the QR code-based game modification learning module for students' motor skills using the ADDIE Development Model is proven to be valid, practical, and effective in the learning process for elementary school students. 1 Sidoharjo.